2013
DOI: 10.5902/217976928476
|View full text |Cite
|
Sign up to set email alerts
|

Educação permanente em saúde na ótica de membros das comissões de integração ensino-serviço

Abstract: RESUMO: Objetivo: conhecer o entendimento dos membros das Comissões de Integração Ensino-Serviço, em relação à participação dos trabalhadores na definição de propostas educativas, fatores que facilitam ou limitam a elaboração e o provimento dos planos regionais e as características das propostas educativas. Método: pesquisa qualitativa, descritiva e exploratória, da qual participaram vinte sujeitos. A análise dos dados seguiu a proposta de análise de conteúdo. Resultados: o cenário indica incipiente participaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
0
6
0
5
Order By: Relevance
“…Difficulties in understanding the concept of permanent education were identified in the publications included in this category, [34][35][36][40][41][42][43][44][45][46][47][48][49] having repercussions in the application to health services. Furthermore, there were challenges for permanent education, in terms of the commitment to professionals and managers.…”
Section: Difficulties In Conceptual Understanding and Application To mentioning
confidence: 99%
See 2 more Smart Citations
“…Difficulties in understanding the concept of permanent education were identified in the publications included in this category, [34][35][36][40][41][42][43][44][45][46][47][48][49] having repercussions in the application to health services. Furthermore, there were challenges for permanent education, in terms of the commitment to professionals and managers.…”
Section: Difficulties In Conceptual Understanding and Application To mentioning
confidence: 99%
“…43 In this respect, the educational practices in the field of mental health stood out, enabling a process of construction of reflective thinking and leading to the perception of other senses and ways in routine production. 48,18 A study conducted with professionals of the Family Health Strategy 49 concluded that higher education professionals did not consider courses and training courses to be capable of producing transformations in their health service practices. This study 49 showed that there are effects of educational actions on team activities, with some orientation towards community reality, although without consistently changing traditional practices.…”
Section: Difficulties In Conceptual Understanding and Application To mentioning
confidence: 99%
See 1 more Smart Citation
“…Sarreta (2009) adverte que o grande desafio é superar a educação como um elemento funcional e ser capaz de ir além dos cursos e treinamentos isolados e voltados para problemas imediatos dos serviços. Nas práticas de saúde, são indispensáveis as propostas educativas reiterativas e tecnicistas, com ênfase em treinamentos, capacitações e cursos em áreas específicas, embora seja fundamental transcender a fragmentação e a descontinuidade (SILVA ET AL., 2013).…”
Section: Dificuldades Na Implantação Das Ciesunclassified
“…Independente das instituições, é fato que as propostas educativas comprometidas com a inovação e a transformação necessitam partir de construções coletivas, embasadas na reflexão e na crítica, que buscam convergir no aprimoramento tanto da assistência como da gestão. 17 O fato de não se enxergarem como membros de uma equipe, com potencial para a busca e socialização do saber, transformando-o em conhecimento, pode prejudicar tanto o desempenho técnico quanto o desenvolvimento pessoal e profissional. Entretanto, os membros da equipe precisam ser vistos como indivíduos que utilizam suas práticas e aprendizados no enfrentamento de cada situação vivenciada, uma vez que eles já conhecem a problemática local.…”
Section: Fatores Que Estimulam Os Profissionais a Participarem Da Epsunclassified